2013
DOI: 10.1194/jlr.m035188
|View full text |Cite
|
Sign up to set email alerts
|

10E,12Z-conjugated linoleic acid impairs adipocyte triglyceride storage by enhancing fatty acid oxidation, lipolysis, and mitochondrial reactive oxygen species

Abstract: This article is available online at http://www.jlr.org adverse conditions, such as systemic and adipose tissue infl ammation, insulin resistance, hepatic steatosis, dyslipidemia, and cardiovascular disease ( 3, 4 ). Representing the major cellular constituent of adipose tissue, adipocytes are now regarded as prominent players in the metabolic as well as hormonal regulation of adiposity. In addition to their primary function of energy storage and release, adipocytes secrete a variety of adipokines and lipid fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
39
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 75 publications
3
39
0
Order By: Relevance
“…Previous in vitro research also showed that a relatively low concentration of t10c12-CLA could induce mammary cancer cell apoptosis (Ou et al 2008). In adipocytes, t10c12-CLA inhibited differentiation (Kang et al 2003), and decreased TG storage by reducing glucose uptake, enhancing lipolysis, and increasing the oxidation of fatty acids (den Hartigh et al 2013). Bcl2 expression is able to enhance drug resistance to cell death, whereas Bax, a partner protein of Bcl2, is a promoter of apoptosis, thus the ratio of Bax/Bcl2 is suggested to determine apoptosis (Stoetzer et al 1996).…”
Section: Discussionmentioning
confidence: 92%
“…Previous in vitro research also showed that a relatively low concentration of t10c12-CLA could induce mammary cancer cell apoptosis (Ou et al 2008). In adipocytes, t10c12-CLA inhibited differentiation (Kang et al 2003), and decreased TG storage by reducing glucose uptake, enhancing lipolysis, and increasing the oxidation of fatty acids (den Hartigh et al 2013). Bcl2 expression is able to enhance drug resistance to cell death, whereas Bax, a partner protein of Bcl2, is a promoter of apoptosis, thus the ratio of Bax/Bcl2 is suggested to determine apoptosis (Stoetzer et al 1996).…”
Section: Discussionmentioning
confidence: 92%
“…We observed a CLA-induced reduction of AT mass was accompanied by hepatomegaly with steatosis. CLA has been shown to decrease TG content in AT by increasing lipolysis caused by the differential expression and localisation of lipid droplet-associated proteins such as perilipin (lipolysis modulation) and adipose differentiation-related protein (lipid storage) (Chung, Brown, Sandberg, & McIntosh, 2005;den Hartigh, Han, Wang, Omer, & Chait, 2013). A decrease in the expression of perilipin, the outer surface lipid droplet protein that serves to protect lipids from hydrolysis by lipases in AT, would increase basal lipolytic activity and decrease fat mass (Tansey et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…This finding therefore has potential significance to human health, because it is this population that is targeted by aggressive marketing of CLA as a weight lowering product, and the available supplements contain both isomers. The t10,c12 CLA isomer is generally believed to be the most active in reducing adipose mass [29][30][31][32]. In these older fa/fa Zucker rats, neither CLA isomer reduced body weight or epididymal fat mass [16].…”
Section: Discussionmentioning
confidence: 98%
“…We also have shown that t10,c12 CLA decreases adipocyte dysfunction by reducing cell size and increasing cell number in epididymal adipose tissue of fa/fa Zucker rats [16,28], and it is generally believed that t10,c12 CLA is responsible for effects on body composition [29][30][31][32]. Animal models of inflammation and obesity have shown that a mixture of CLA isomers increases antiinflammatory cytokines and decreases proinflammatory cytokines [33][34][35][36].…”
Section: Introductionmentioning
confidence: 90%